2016
DOI: 10.1017/s0007114516001938
|View full text |Cite
|
Sign up to set email alerts
|

Cereal fibre intake and risk of mortality from all causes, CVD, cancer and inflammatory diseases: a systematic review and meta-analysis of prospective cohort studies

Abstract: Dietary fibre intake has been associated with a lower risk of mortality; however, findings on the association of different sources of dietary fibre with mortality are conflicting. We performed a systematic review and meta-analysis of the prospective cohort studies to assess the relation between cereal fibre intake and cause-specific mortality. Medline/PubMed, SCOPUS, EMBASE, ISI web of Science and Google scholar were searched up to April 2015. Eligible prospective cohort studies were included if they provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 36 publications
0
53
0
1
Order By: Relevance
“…Studies performed in the last years [1][2][3]7,9], showed that DF intake was below the recommended value, and the prevalence of cancer and obesity increased in the last decade, data that sustain the need for proper educational intervention and an updated national food-based dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies performed in the last years [1][2][3]7,9], showed that DF intake was below the recommended value, and the prevalence of cancer and obesity increased in the last decade, data that sustain the need for proper educational intervention and an updated national food-based dietary guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recommendations, worldwide the quantity of dietary fibers in the menus is low, being influenced by cultural changes and preferences for eating out-home, by urbanisation, by more refined and processed types of food on the market, economic development along with new western-type diet trends and lack of information on this topic. Consequently, these changes have been associated with an increase in the global prevalence of non-communicable diseases and even mortality [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective role of the MedDiet against these health outcomes has also been shown consistently in the long-term PREDI-MED (2003 randomised trial (Babio et al, 2014;Buil-Cosiales et al, 2016). A reason explaining why the MedDiet influences our health positively has been attributed to its low-glycaemic properties and dietary fibre (DF) content that is associated with bioactive ingredients (Babio et al, 2014;Buil-Cosiales et al, 2016;Salas-Salvadó et al, 2016) Recent studies highlight that specific cereal fibre may have a positive impact on human health (Evans et al, 2015;Liu et al, 2015;Aune et al, 2016;Hajishafiee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another recent meta-analysis of cohort studies (9) reported that cereal fiber intake was associated with lower risk of all-cause, CVD, and cancer mortality. Some, but not all (10)(11)(12), earlier investigations showed an inverse association between whole-grain intake and mortality.…”
Section: Introductionmentioning
confidence: 99%